2005
DOI: 10.1111/j.1600-0579.2004.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress, burnout and health in the clinical period of dental education

Abstract: The study examined the extent of stress, burnout and health problems experienced by fourth and fifth year dental students from the three universities of Dresden, Freiburg and Bern. The objectives of the study were to: (i) identify frequent sources of stress and to report the prevalence rates of burnout and health problems in dental students, (ii) determine the rate of students suffering from severe burnout symptoms and (iii) identify stress factors related to the burnout symptoms of emotional exhaustion and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
228
2
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(270 citation statements)
references
References 16 publications
10
228
2
11
Order By: Relevance
“…42,43 Además del estrés y el agotamiento reportado en numerosos estudios sobre estudiantes de carreras de odontología en el mundo, [44][45][46] también se ha demostrado que estos reconocen tener conductas poco profesionales debido a la presión que ejerce la carrera, donde la atención al paciente se ve solo como un programa a cumplir, con requerimientos que hay que sortear de manera inflexible. Todos estos aspectos irían en contra de un ambiente de integridad propicio para generar conductas ligadas al profesionalismo.…”
Section: Clima Educativo Y Rol Del Docenteunclassified
See 1 more Smart Citation
“…42,43 Además del estrés y el agotamiento reportado en numerosos estudios sobre estudiantes de carreras de odontología en el mundo, [44][45][46] también se ha demostrado que estos reconocen tener conductas poco profesionales debido a la presión que ejerce la carrera, donde la atención al paciente se ve solo como un programa a cumplir, con requerimientos que hay que sortear de manera inflexible. Todos estos aspectos irían en contra de un ambiente de integridad propicio para generar conductas ligadas al profesionalismo.…”
Section: Clima Educativo Y Rol Del Docenteunclassified
“…42,43 In addition to the stress and fatigue reported in numerous studies on dental students worldwide, [44][45][46] it has been shown that they recognize behaving in a not very professional manner due to the pressures of the course of studies, where patient care is seen only as a program to be met, with requirements that need to be inflexibly sorted out. All these aspects go against a suitable environment of integrity to generate professional behaviors.…”
Section: Educational Climate and Professor's Rolementioning
confidence: 99%
“…Given that MBI-SS is the most used instrument worldwide for this Syndrome's screening, that its metric qualities have been considered adequate and stable in several studies [7][8][9][10][11]21 , and given the lack of a 'gold standard' for diagnosis of Burnout, we decided to consider the MBI as the 'gold standard' in this study, as previously recommended by Schutte et al 22 (2000).…”
Section: Study's Variablesmentioning
confidence: 99%
“…According to the literature 6,[8][9][10][11] the assessment of the Burnout Syndrome has occurred in parallel with the evolution of its concept, being the Maslach Burnout Inventory (MBI) the most used instrument in burnout assessment.…”
mentioning
confidence: 99%
“…2 Stress is a significant threat that can result in physical or mental illness, and may have a strong negative effect on student's academics and their consecutive practice in dentistry. 3 stress can lead to anxiety, depression, decreased work efficiency and burn out in dental students 4 . Dentists suffer from especially high degrees of stress even when compared with other health professions [5][6] In the literature so many stress related studies for dental students available.…”
Section: Introductionmentioning
confidence: 99%